2021
DOI: 10.1016/j.omega.2019.102112
|View full text |Cite
|
Sign up to set email alerts
|

Proactive transshipment in the blood supply chain: A stochastic programming approach

Abstract: The main objective when managing inventories in blood supply chains is to establish an efficient balance between the wastage and shortage of blood units. The uncertain demand and the perishable nature of blood units can result in over-or under-stocking and increase wastage and shortage costs. In this study, we analyze how a proactive transshipment policy can avoid future shortages in addition to mitigate wastage. We consider a network of hospitals with uncertain demand in which each hospital makes decisions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 86 publications
(98 reference statements)
0
46
0
Order By: Relevance
“…Dehghani et al. [33] proposed a stochastic mathematical model for blood supply chain management. Considering proactive transshipment and order quantities simultaneously was one of the key novelties in their research.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehghani et al. [33] proposed a stochastic mathematical model for blood supply chain management. Considering proactive transshipment and order quantities simultaneously was one of the key novelties in their research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with the research carried out by Dehghani et al. [33] , our research took the advantage to investigate the transportation capacity and substitution priority accompanied with a real case study. Besides, locating collection centers and allocating centers to hospitals are considered of other study advantages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the above categories interdependency, some of the most recent researches attempted to tackle this problem more comprehensively by integrating them (Hosseini-Motlagh et al 2020a;Karadağ et al 2021;Dehghani et al (2021).…”
Section: Blood Supply Chain Planningmentioning
confidence: 99%
“…Different facilities in the same echelon can share their blood storage using this feature to decrease blood shortage while using the same limited stock of blood units. Some researchers have recently implemented this policy successfully (Dehghani et al 2021;Ghatreh Samani and Hosseini-Motlagh 2021). However, the mentioned studies only considered this policy in hospitals and did not extend it to blood centers, which sounds necessary, especially during a disaster.…”
Section: Blood Supply Chain Planning For Disaster Reliefmentioning
confidence: 99%
“…The third group of constraints ( 9)-( 14) models the flow and the inventory of bloodderived products, and are mostly based on the formulation described by Dillon et al (2017). An interesting study could be to use a more recent way of modelling inventory proposed by Dehghani et al (2019), which showed potential to reduce computational times. Constraints ( 9) and ( 10) are flow conservation constraints for bloodderived products and, essentially, they ensure that products produced/purchased in a given period which are not transported, in case of constraints (9), or consumed, in case of constraints (10), are kept as inventory at processing centres or demand zones, respectively.…”
Section: Mathematical Modelmentioning
confidence: 99%